2022
DOI: 10.1007/s11325-022-02597-z
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic role of ultrasound and magnetic resonance imaging in obstructive sleep apnoea based on lateral oropharyngeal wall obstruction

Abstract: Purpose This study examined the prognostic value of the lateral pharyngeal wall (LPW)-based obstruction and obstructive sleep apnoea (OSA) prediction using ultrasound (US) and MRI (magnetic resonance imaging). Methods One hundred patients with and without OSA were enrolled, according to overnight polysomnography. The LPW thickness (LPWT) was measured using a Philips Ingenia 1.5 T MRI device, and US measurements were carried out at rest and during Müller’s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Contrary to previous work [ 36 ], both the lateral and anterior–posterior diameters were found smaller in OSA subjects in [ 37 ]; this could be due to the small sample size in the study reported in [ 36 ], noting that, although the difference in lateral diameter was significant, it was smaller than the difference in anterior–posterior diameter. Furthermore, 2D soft tissue measurements showed that the lateral pharyngeal wall was larger in OSA subjects and was associated with an increased risk of OSA [ 32 ]; this is congruent with the findings in [ 32 ] using 1.5-T MRI that showed larger LPW thickness in OSA group, while the associated risk of the volumetric measurements was substantially greater [ 32 ].…”
Section: Methodssupporting
confidence: 77%
See 4 more Smart Citations
“…Contrary to previous work [ 36 ], both the lateral and anterior–posterior diameters were found smaller in OSA subjects in [ 37 ]; this could be due to the small sample size in the study reported in [ 36 ], noting that, although the difference in lateral diameter was significant, it was smaller than the difference in anterior–posterior diameter. Furthermore, 2D soft tissue measurements showed that the lateral pharyngeal wall was larger in OSA subjects and was associated with an increased risk of OSA [ 32 ]; this is congruent with the findings in [ 32 ] using 1.5-T MRI that showed larger LPW thickness in OSA group, while the associated risk of the volumetric measurements was substantially greater [ 32 ].…”
Section: Methodssupporting
confidence: 77%
“…Another research examined the prognostic value of the lateral pharyngeal wall’ (LPW) thickness for the detection of OSA using two both US and MRI [ 32 ]. One hundred individuals with and without OSA (36 healthy controls and 64 OSA subjects) were enrolled in the study and performed an overnight PSG, and then the LPW thickness was measured using 1.5-T MRI and ultrasound during wakefulness.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations